Sorghum seed maturity affects the weight and feeding duration of immature corn earworm, Helicoverpa zea, and fall armyworm, Spodoptera frugiperda, in the laboratory - Soper, Alysha M.; Whitworth, R. Jeffery; McCornack, Brian P. (My University, 2013)
Corn earworm, Helicoverpa zea Boddie (Lepidoptera: Noctuidae), and fall armyworm, Spodoptera frugiperda J.E. Smith, are occasional pests in sorghum, Sorghum bicolor L. Moench (Poales: Poaceae), and can be economically damaging when conditions are favorable. Despite the frequent occurrence of mixed-species infestations, the quantitative data necessary for developing yield loss relationships for S. frugiperda are not available. Although these species share similar biological characteristics, it is unknown whether their damage potentials in developing grain sorghum panicles are the same. Using no-choice feeding assays in the laboratory, this study examined larval growth and feeding duration for H. zea and S. frugiperda in the absence of competition. Each species responded positively when exposed to sorghum seed in the soft-dough stage, supporting evidence for the interactions between host-quality and larval growth and development. The results of this study also confirmed the suitability of using laboratory-reared H. zea to develop sorghum yield loss estimates in the field, and provided insights into the biological responses of S. frugiperda feeding on developing sorghum seed.
Citation: Soper AM, Whitworth RJ, McCornack BP. 2013. Sorghum seed maturity affects the weight and feeding duration of immature corn earworm, Helicoverpa zea, and fall armyworm, Spodoptera frugiperda, in the laboratory. Journal of Insect Science 13:67. Available online: http://www.insectscience.org/13.67
Keywords: Food consumption; Grain sorghum; Larval growth; Phenology; Sorghum bicolor; Corn earworm; Fall armyworm